EXPLORATION OF IRRATIONAL BELIEFS OF PRISONERS WHO EXPERIENCE ANXIETY BEFORE RELEASE - Novianti, Nabilah; Hamzah, Imaduddin (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to explore the irrational beliefs experienced by prisoners at the Class IIA Jember Correctional Institution, specifically related to anxiety that arises before release. Prisoners often face psychological disorders, including anxiety, which are triggered by various factors, such as the length of the sentence and uncertainty about life after release. The research method used was qualitative with a case study approach, involving three prisoners who experienced anxiety before release. The results of the interviews revealed the existence of irrational thought patterns, such as catastrophizing, where prisoners imagine the worst scenario related to social rejection and difficulty adapting after returning to society. The findings show that the anxiety experienced by prisoners is closely related to two types of irrational beliefs, namely catastrophizing and personalization, which contribute to increased anxiety that interferes with prisoners' mental health. Keywords: Irrational Belief ; Prisoners ; Anxiety Ahead of Release